Human detection thresholds of DC, AC, and hybrid electric fields: a double-blind study - Michael Kursawe; Dominik Stunder; Thomas Krampert; Andrea Kaifie; Sarah Drießen; Thomas Kraus; Kathrin Jankowiak (BMC, 2021)
Abstract Background In the course of the ongoing transition of electric energy systems, transmission corridors are often upgraded to higher voltages and other technologies leading to another quality of human exposure. The study aims to determine human detection thresholds for direct current (DC), alternating current (AC), and hybrid electric fields (various DC; constant AC). Methods A total of 203 participants were exposed to DC, AC, and hybrid electric fields (EFs) in a highly specialized whole-body exposure laboratory using a double-blind experimental setting. Additionally, the participants were exposed to ion currents in part of the DC and hybrid sessions. To investigate environmental influences, relative humidity was changed in two subgroups during EF perception. Methods derived from the signal detection theory and the adaptive staircase procedure based on the single interval adjustment matrix were used to assess individual sensitivity and detection thresholds, respectively. Results The results indicated that detection thresholds of hybrid EF were lower compared to single EF presentation of DC or AC. Ion current exposure enhanced EF perception. High relative humidity facilitated DC EF perception, whereas low relative humidity reinforced the perception of AC EFs. Conclusions With this systematic investigation of human perception of DC, AC, and hybrid EFs, detection thresholds were provided, which can help improve the construction processes of energy transmission systems and the prevention of unwanted sensory perception by contributing to the determination of limit values.